Pesca esportiva na região neotropical: situação atual, perspectivas futuras e um estudo de caso - Ladislau, Daniel da Silva (2022)
Recreational fishing has been increased around the world, due to the increase in the number of practitioners, mainly in developed countries, which has generated millions in financial income through the trade of products and services. In countries with emerging economies, such as Brazil, recreational fishing has become an important instrument for economic, social and ecological development in several regions, whether through amateur fishing tourism or its other segments. Despite the recognition of the social and economic importance of this activity in the world and national scenario, there is a lack of information about this activity in different regions, such as in countries of the Neotropical region. In addition, there are few studies aimed at the segment of competitive fishing and its practitioners in the region, especially on sport fishing tournaments in lentic environments, such as reservoirs. Therefore, this study sought to investigate the situation of recreational fishing in the neotropical region, as well as some issues and problems faced by the sector. We seek to answer the following questions about recreational fishing in the region: a). What is the current scenario and challenges of recreational fishing in neotropical countries? b) What are the socio-economic aspects of sport fishermen participating in fishing tournaments in a reservoir in the neotropical region? c) What are the characteristics of the fisheries of competitive fishing tournaments in a reservoir in the neotropical region? The results indicated that articles related to recreational fishing are increasing significantly over the years in the Neotropical region. However, there are some challenges around recreational fishing, such as the generation of negative effects, especially the overexploitation of local fish stocks. They also demonstrated that the sport fishing tournaments in the Itaipu reservoir are different, with significant differences between the socio-economic profile of sport fishermen of tucunaré and corvina. We conclude that recreational fishing studies are in full growth in the Neotropical region, a trend that will be maintained in the coming years. And the sport fishing tournaments in the Itaipu reservoir have different patterns, influenced by the social and economic variables of the participants, as well as the characteristics of the fisheries.